Entrepreneurship, bureaucracy and administrative procedures: “anti-commons tragedy” in the Portuguese aquaculture sector - Filipe, J. A.; Coelho, M. P.; Ferreira, M. A. M. (Journal of Applied Management and Investments (JAMI), 2013)
“Anti-commons” is seen as a property regime in which multiple owners hold ef-fective rights of exclusion in a scarce resource. The coexistence of multiple exclusion rights creates conditions for suboptimal use of the common resource. The anti-commons construction offers an analytical tool for isolating a central feature of “some-times disparate institutional structures”. Accordingly, inefficiencies introduced by overlapping and intrusive regulatory bureaucracies may be studied with the help of this conceptualization. When an entrepreneur seeks to invest in a project and his action is inhibited by the necessity of getting permits from several national and regional agen-cies, each one holding exclusion rights to the project, a “tragedy of the anti-commons” may happen. Consequently, a lot of problems in the development of local initiatives of entrepreneurship emerge, affecting the potential of innovation and affecting the re-gional development. There are only a few empirical studies on anti-commons tragedies in the real world, most of them focusing on pharmaceutics industry. The main purpose of this paper is to use this conceptualization to study the design and execution of aqua-culture policy in Portugal and to introduce the possible emergence of an “anti-commons tragedy” when we approach the difficult process of approval and execution of projects of aquaculture in the Portuguese coastal areas. Our results are consistent with the suggestion of Buchanan and Yoon (2000).